Report on Candidates' Work in the Secondary Education Certificate General and Basic Examinations June 1990: Clothing and Textiles - Caribbean Examinations Council (CXC, 1990)
This report provides general and detailed comments on the performance of candidates in the June 1990 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Clothing and Textiles.
Keywords: CXC CSEC examinations